The Political Economy of Social Security - Georges Casamatta; Helmuth Cremer; Pierre Pestieau (Center for Economic Studies and ifo Institute (CESifo), 2000)
We consider a two-period overlapping generations model in which individual voters differ by age and by productivity. In such a setting, a redistributive Pay-As-You-Go system is politically sustainable, even when the interest rate is larger than the rate of population growth. The workers with medium wages (not those with the lowest wages) and the retirees form a majority which votes for a positive level of social secur ity. This level depends on the difference between population growth and interest rate and on the redistributiveness of benefit rule.
Keywords: 330; Social security; majority voting